FLOOD HAZARD ASSESSMENT AND COPING MECHANISM OF A LOCAL COMMUNITY (A Case Study in District of Tenggarong, Regency of Kutai Kartanegara, Province of Kalimantan Timur) - , LIDYA LESTARI SITOHANG, Dr. rer. net. Muh. Aris Marfai, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research is conducted due to The 2010 flood in the District of Tenggarong was triggered by high precipitation which started on March 28 and continued until March 29, 2010. Thus, general objectives of that this study is to derived what the community embraced in response to the flood hazard. Furthermore, based on this general objective, three elaborated objectives are to identify the predominant cause of the 2010 flood hazard in the study area, to study the communityâs perception in regards to the 2010 flood hazard as well as t analyze the coping mechanism of the community in response to the 2010 flood hazard. Methods carried out in this study are divided due to the three phases of the research i.e. pre-fieldwork which had purposively selected the study area, fieldwork that occupied interview and semi structured interview, and the post fieldwork that mainly is a phase analysis process and utterly produced the result of this study. Due to the achieved objects of this research, the gained results are as follow